Female judges in Islamic courts: determinants of the juristic positions - Muhsin, Sayyed Mohamed (2022)
Regarding the validity female judgeship, Islamic jurists have adopted three different positions. The first group, which is of majority, rejected female judgeship while the second allowed it with restrictions. The third group validated female judgeship as lo ng as they fulfil the general criteria without heeding gender differences. This article attempts to investigate the potential reasons behind the various juristic positions, exploring the counterarguments and practices on the ground.